Skill acquisition practices of coaches on the British Para swimming World Class Programme - Powell, D.; Wood. G.; Kearney, P.; Payton, C. (International Journal of Sports Science & Coaching, 2021)
This study set out to gain insight into the practices adopted by elite level Paralympic swimming coaches and to shed light on the knowledge and rationale underpinning their approaches. Coaching sessions were delivered by nine senior coaches from the British Para swimming (BPS) World Class Programme. A coaching session was observed from each coach and a semi-structured interview was recorded and transcribed to explore their intentions and rationale for the structure and content of the session delivered. Results indicated that coaches: (i) predominantly emphasised internal focus instruction and feedback cues, (ii) incorporated relatively low levels of between-skill variability and higher levels of within-skill variability, and (iii) applied mostly explicit learning techniques such as part-task training and verbal feedback, but also incorporated some implicit learning techniques such as analogies and constraints-based learning. Interview data indicated coaches had limited knowledge of key skill acquisition principles. The study serves to highlight potential gaps in understanding on the side of both research and applied practice in the hope of facilitating future collaborations between coaches and skill acquisition practitioners.